IMPLEMENTASI MEDIA BLOOD SIRCULATION UNTUK MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI SISTEM PEREDARAN DARAH MANUSIA BAGI SISWA KELAS V DI MADRASAAH IBTIDAIYAH MIFTAHUL ULUM DERO KESAMBEN JOMBANG - Muhsin, Ali; Arifin, Zainal (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
This research is to improve the ability to identify human circulatory system of SCIENCE class V subjects at MI Miftahul Ulum Dero Kesamben Jombang which uses Blood Sirculation media, implemented in 2 cycles. Researchers use PTK, researchers took the class V of MI Miftahul Ulum Dero Kesamben Jombang with 20 students consisting of 12 men, 8 women. In the pre-cycle stage teachers still use conventional methods, so that only 2 students are able to achieve a classical survival with a percentage of 15%, average classification 42.50. After the media, Blood Sirculation in Cycle 1 experienced an increase of 25% with 12 skilled students. In Cycle 2 The students experience an increase significantly evidenced by the classical averages reaching 78 with a percentage of the 99.05% compensation. Therefore it was concluded that the SCIENCE learning in identifying the human circulatory system with Blood Sirculation is able to improve the ability to identify human circulatory system students class V MI Miftahul Ulum Dero Kesamben Jombang.